Development of Method to Determine C6-C3 Phenolic Acids in Tobacco (Nicotiana tabacum) by HPLC - Zhao, Huina; Cai, Kai; Lei*, Bo; Ren, Zhu; Cai, Bin; Pan*, Wenjie (Asian Journal of Chemistry, 2014)
A method to simultaneous determination of four C6-C3 phenolic acids in tobacco by high performance liquid chromatography (HPLC) was established. Four C6-C3 phenolic acids were well separated in 40 min. The proposed method had high sensitivity, accuracy and repeatability with good linear relationship (R2 ³ 0.9992) when the concentration of phenolic acids was between 1.113 and 102.332 μg/mL. This method was applied to tobacco samples. The results showed that the content of four C6-C3 phenolic acids was significantly different in tobacco at different regions and growth stages, and the contents of p-coumaric acid, ferulic acid and sinapic acid in tobacco were influenced by the ecological conditions more than growth stages. This might be one of the reasons that the tobacco leaves in different regions had different quality.